Risk factors for postoperative pancreatic fistula: Analysis of 170 consecutive cases of pancreaticoduodenectomy based on the updated ISGPS classification and grading system. Issue 35 (August 2018) - Ke, Zunxiang; Cui, Jing; Hu, Nianqi; Yang, Zhiyong; Chen, Hengyu; Hu, Jin; Wang, Chunyou; Wu, Heshui; Nie, Xiuquan; Xiong, Jiongxin
Abstract : Abstract: This study was designed to analyze the risk factors for postoperative pancreatic fistula (POPF) after pancreaticoduodenectomy (PD). Between September 2015 and August 2017, 170 successive patients underwent a radical PD in the Department of Pancreatic Surgery, Union Hospital, Wuhan. We carried out a retrospective study of these cases and the prospective conditions, which might be related to POPF, were examined with univariate and multivariate analysis. POPF was defined as a drain output of any measurable volume of fluid with an amylase level more than 3 times the upper limit of serum amylase activity on postoperative day 3, accompanied by a clinically relevant condition according to the 2016 update of the International Study Group for Pancreatic Surgery (ISGPS) definition. In our study, the POPF was just referred to as grade B and grade C pancreatic fistula in accordance with the ISGPS consensus, because the former grade A pancreatic fistula is now redefined as a biochemical leak, namely no-POPF, which has no clinical impact and needs no other special therapy. Pancreatic fistula occurred in 44 (25.9%) patients after PD, with a mean length of hospital stay of 24.98 ± 14.30 days. Thirty-six patients (21.2%) developed grade B pancreatic fistula, and 8 patients (4.7%) had grade C pancreatic fistula. Among patients with grade C pancreatic fistula, 4 patients died, 3 patients were operated on again, and 3 patients developed multiple organ failure. Univariate analysis showed a significantly important association between POPF and the following factors: pancreas texture (soft vs hard: 39.1% vs 10.3%, P  < .0001) and fasting blood glucose level (<108.0 mg/dL vs ≥108.0 mg/dL: 32.5% vs 12.5%, P  = .005). Multivariate logistic regression analysis identified 2 independent factors related to POPF: soft pancreas texture and fasting blood glucose level <108.0 mg/dL. A soft pancreas and a fasting blood glucose level of <108.0 mg/dL are risk factors for the development of a POPF.